Enhanced wound healing using a 3D printed VEGF-mimicking peptide incorporated hydrogel patch in a pig model. (9th April 2021) - Jang, M J; Bae, S K; Jung, Y S; Kim, J C; Kim, J S; Park, S K; Suh, J S; Yi, S J; Ahn, S H; Lim, J O
Abstract: There is a need for effective wound healing through rapid wound closure, reduction of scar formation, and acceleration of angiogenesis. Hydrogel is widely used in tissue engineering, but it is not an ideal solution because of its low vascularization capability and poor mechanical properties. In this study, gelatin methacrylate (GelMA) was tested as a viable option with tunable physical properties. GelMA hydrogel incorporating a vascular endothelial growth factor (VEGF) mimicking peptide was successfully printed using a three-dimensional (3D) bio-printer owing to the shear-thinning properties of hydrogel inks. The 3D structure of the hydrogel patch had high porosity and water absorption properties. Furthermore, the bioactive characterization was confirmed by cell culture with mouse fibroblasts cell lines (NIH 3T3) and human umbilical vein endothelial cells. VEGF peptide, which is slowly released from hydrogel patches, can promote cell viability, proliferation, and tubular structure formation. In addition, a pig skin wound model was used to evaluate the wound-healing efficacy of GelMA-VEGF hydrogel patches; the results suggest that the GelMA-VEGF hydrogel patch can be used for wound dressing.